Planering av väginvesteringar - Myhrman, Joakim (SLU/Dept. of Forest Resource Management, 2007)
The problems around and the planning of wood flow is some of the most complex issues in the forest-sector. The experience and overview of the single employees is crucial for the possibility of correct tactical and economical decision-making. The increasing demand of savings and shorter reaction-times with greater flexibility in the wood-supply-chain, makes solutions and aids for improved effectiveness in the work and processes according to wood-flow urgent.